Аппроксимативные свойства операторов типа Абеля−Пуассона на обобщенных классах Гельдера - Харкевич, Ю.И.; Ханин, А.Г. (Проблемы управления и информатики, 2021)
Роботу присвячено актуальним проблемам сучасної прикладної математики, а саме вивченню апроксимативних властивостей операторів типу Абеля-Пуассона на так званих узагальнених класах функцій Гельдера. The work is dedicated to the current problems of modern applied mathematics, specifically the study of approximation properties of Abel-Poisson type operators on so-called generalized Hölder classes of functions.